The Relationship between the Qur’an and the Sunnah (American Journal of Islam and Society, 2010)
From 25 July to 6 August 2010, a select group of scholars invited by the InternationalInstitute of Islamic Thought (IIIT) analyzed “The Relationshipbetween the Qur’an and the Sunnah.” Chaired by Mahmoud Ayoub (HartfordSeminary), this twenty-session event focused on how Muslims are dealingwith Islam’s two core sources in the twenty-first century